Frontispiece: Anisotropic Expansion of an M2L4 Coordination Capsule: Host Capability and Frame Rearrangement. Issue 11 (9th March 2015) - Yamashina, Masahiro; Yuki, Tsubasa; Sei, Yoshihisa; Akita, Munetaka; Yoshizawa, Michito
<x xml:space="preserve">Abstract</x> Host–Guest Systems Anisotropic expansion of a spherical M2L4 coordination capsule through the elongation of the ligand led to a new M2L′4 capsule. The expanded capsule provides an elliptical cavity encircled by polyaromatic frameworks with large openings and thereby can encapsulate elliptical fullerene C70 and monofunctionalized fullerene C60 in high yields. For more information see the Communication by M. Yoshizawa et al. on page 4200 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>